Household Budgets Among Different Income Groups in Klang Valley - Buhari, Al Sarah Alyaa Al; Supian, Kamisah; Abdullah, Sharifah Hilmi Syed (Journal of Accounting, Business and Management (JABM), 2024)
Budgeting is a common approach financial advisors introduce to teach individuals how to manage their expenses. Without budgeting, however, family living expenses may exceed the available income and jeopardise the family's overall financial goals. Financial issues are one of the significant causes of instability among families, especially lowincome earners who live below the usual standard and have an income that can only go for food and housing, making it impossible to satisfy their family's needs and attain goals. This scenario puts low-income families in a problematic state or condition that can be resolved through adequate financial support. This study examines the dynamics of household budgeting practices across various income groups within the Klang Valley region. The study also aims to identify the importance of budget allocation and expenditure priorities among low-income, middle-income, and high-income households. It underscores the crucial role of financial literacy and planning factors in budgeting practices, empowering individuals with the knowledge to manage their finances effectively. Data were collected from 65 tourism industry workers with multiple backgrounds by distributing questionnaires using a convenient sampling approach. The data collected were analysed using the Statistical Package for Social Science (SPSS) software. The findings contribute to a better understanding of how income disparities shape household finances and inform policy interventions to enhance financial resilience and equity within the Klang Valley community.